The gut–kidney axis is regulated by astragaloside IV to inhibit cyclosporine A-induced nephrotoxicity - Han, Cong; Gao, Ran-ran; Zhou, Le; Li, Wei (Frontiers in Pharmacology, 2025)
IntroductionChronic nephrotoxicity caused by CNIs (CICN) manifests clinically as chronic kidney disease (CKD). Astragaloside IV (AS-IV) plays a certain role in the treatment of CKD. This study aimed to verify the ameliorative effects of AS-IV on CICN and further explore the mechanisms underlying the modulation of the “gut–transcriptome–metabolome coexpression network” by AS-IV within the context of the “gut–kidney axis” to improve CICN.MethodsFive groups of 40 mice were studied: a normal group (N, olive oil), a model group (M, CsA, 30 mg kg-−1 d−1), a low-dose AS-IV group (CsA + AS-IV, 30 mg kg−1 d−1 + 10 mg kg−1 d−1), a high-dose AS-IV group (CsA + AS-IV, 30 mg kg−1 d−1 + 20 mg kg−1 d−1), and a valsartan group (CsA + Val, 30 mg kg−1 d−1 + 10 mg kg−1 d−1). The gut microbiota, renal transcriptome, and urine metabolome were separately detected to construct a gut–transcriptome–metabolome coexpression network. The target species, target genes, and target metabolites of AS-IV were evaluated.ResultsCsA led to increased proteinuria and a deterioration of kidney function, accompanied by increased inflammation and oxidative stress, whereas AS-IV improved kidney damage. AS-IV inhibited intestinal permeability and disrupted the microbiota structure, increasing the abundance of Lactobacillus reuteri, Bifidobacterium animalis, Ignatzschineria indica, and Blautia glucerasea. Six coexpression pathways related to transcription and metabolism, including the citrate cycle, ascorbate and aldarate metabolism, proximal tubule bicarbonate reclamation, glycolysis/gluconeogenesis, ferroptosis, and drug metabolism–cytochrome P450, were identified. Seven target metabolites of AS-IV were identified in the 6 pathways, including UDP-D-galacturonic acid, 2-phenylethanol glucuronide, dehydroascorbic acid, isopentenyl pyrophosphate, alpha-D-glucose, 3-carboxy-1-hydroxypropylthiamine diphosphate and citalopram aldehyde. Five target genes of AS-IV, Ugt1a2, Ugt1a9, Ugt1a5, Pck1, and Slc7a11, were also identified and predicted by NONMMUT144584.1, MSTRG.30357.1 and ENSMUST00000174821. Lactobacillus reuteri was highly correlated with renal function and the target genes and metabolites of AS-IV. The target genes and metabolites of AS-IV were further validated. AS-IV inhibited intestinal-derived urinary toxins and improved renal tissue apoptosis, lipid accumulation, collagen deposition, and mitochondrial damage.ConclusionAS-IV improved CICN through the coexpression of the gut–transcriptome–metabolome network. The six pathways related to energy metabolism driven by L. reuteri, including the citrate cycle, ascorbate and alderate metabolism, proximal tube bicarbonate metabolism, glycolysis/gluconeogenesis, ferroptosis, drug metabolism–cytochrome P450, are important mechanisms.